SENAM LANSIA DALAM UPAYA MENINGKATKAN KEBUGARAN JASMANI LANSIA - Riyanto, Pulung; Koten, Yoseph Cannisius; Lahinda, Jori (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the level of change in elderly exercise in an effort to improve the physical fitness of the elderly at the Rimba Jaya Health Center.This research is a type of quasi-experimental research (quasi-experimental design), with a sampling technique using purposive sampling as many as 25 elderly consisting of 2 posyandu namely wasur 1 and wasur 2. The instrument in this study used a physical fitness test in the form of a walking test. 6 minutes. Data collection techniques using physical fitness tests. The data analysis technique used SPSS 22 software with prerequisite tests and hypothesis testing (t test).The results showed that there were significant changes in elderly exercise in an effort to improve the physical fitness of the elderly at the Rimba Jaya Health Center. This is shown from the sig value of the data calculated between the posttest results and the pretest results is 0.000 which means it is smaller than 0.05 (0.000 <0.05). So, it can be concluded that efforts to increase the physical fitness of the elderly through elderly gymnastics have an effect on improving the physical fitness of the elderly at the Rimba Jaya Health Center. The posttest mean value is greater than the posttest mean value or (29.3220>26.6924).